Initial coin offering: effective instrument for companies or speculation? - Paradiso, Francesco Lovanio (2020)
The advent of Block chain technology has led in recent years to the birth of a new form of capital raising, the Initial Coin Offering(ICO), through which start ups finance them selves through the issuance of digital tokens. As of 2017, this phenomenon has exploded, both in the number of ICOs conducted and in the amount of capital raised, thus attracting the attention of many. In this paper will be described and analysed the main aspects related to ICO, starting first of all with the technologies underlying the phenomenon, Blockchain and Distributed Ledger Technology. In this phase, a focus will be made on the crypto currencies and their uncertain future.Then, it will be explained its characteristics, functioning and phases, and the comparison with traditional fundraising methods: Initial Public Offering (IPO), Crowdfunding, Venture Capital and Business Angels. In the final part of the paper it will be analyzed the ICO market: its evolution over time, the main features in terms of concentration and an analysis of the performance. The results of the empirical analysis carried out on a sample of 365ended ICOs from 2014 to 2018, will reveal how the performance of this new method of raising capital are not encouraging at all, with a largely negative average return (-45%) and with 86%of the cases in which the current price of the tokens is below their listing price. The paper will conclude by discussing the implications of the empirical results obtained, above all with respect to regulatory aspects, which still lack of a global harmonization and that will be a key point for the future of this new financing method.